The experiences of facility-based counsellors who provide a psychosocial intervention for mental illness in primary healthcare facilities in the Western Cape - Jacobs, Yuche Andy (University of Cape Town, 2020)
Background: Despite the movement in global mental health that advocates for task-sharing, few studies have investigated the experiences of facility-based counsellors (FBCs) who provide a psychosocial intervention for mental illness in primary healthcare. Project MIND, a cluster-randomized controlled trial at 24 primary healthcare facilities in the Western Cape, trained FBCs to deliver a threesession evidence-based intervention for patients with a common mental disorder. Therefore, project MIND presents an opportunity to address a gap in the literature by exploring the experiences and needs of FBCs delivering a psychosocial intervention. Aims & Objectives: The overall aim of this study is to explore the experiences of FBCs working on Project MIND in the dedicated (training and adding a counsellor to the chronic disease team) and designated (training and using existing counsellor from the chronic disease team) intervention arms. Specific objectives included: (1) exploring the barriers and challenges that FBCs experienced while delivering a psychosocial intervention; (2) exploring FBCs' perceptions of regular structured supervision, debriefing and in-service training for improving micro-counselling skills; and (3) eliciting suggestions from the FBCs for future scale up of counselling services in primary healthcare settings. Methods: A qualitative study was conducted among FBCs delivering the project MIND psychosocial intervention (N=18). All interviews were conducted by an independent qualitative interviewer in a private room at the primary healthcare facilities. Interviews were audio-recorded and transcribed verbatim. NVivo 12 was used to store data and facilitate analysis using the Framework Approach. Results: Findings of the study were grouped according to four main themes. The first theme focused on FBCs' perceptions of the benefits of the project MIND training. Several perceived benefits were reported such as having a better understanding about mental illness particularly depression, enhanced counselling skills and transferability of skills to other daily duties in the healthcare facility. Role-playing stood out as a key training component to assess counselling readiness. The second theme focused on barriers and facilitators related to the implementation of the project MIND intervention. Designated FBCs reported competing task demands as a barrier to implementing the MIND intervention compared to designated FBCs. Further, most designated counsellors reported feeling marginalized in the facility due to their lowly status. Other barriers reported which impacted on their motivation to implement the MIND intervention by both dedicated and designated FBCs were low remuneration, a lack of counselling space, and a lack of privacy and confidentiality. Regarding facilitators to implementing the MIND intervention, experiencing first-hand how well patients were able to solve some of their problems using the problem-solving method and taking responsibility for their health motivated FBCs to implement the MIND intervention. In addition, the MIND intervention aided FCBs with solving their own problems which enhanced their belief in the effectiveness of the intervention. The third theme dealt with how FBCs perceive the clinical supervision and debriefing provided by project MIND. Regular structured supervision, debriefing and in-service training delivered by a registered psychological counsellor, a novel approach, was perceived as beneficial to all FBCs as it provided them with a means to reassess and improve their counselling skills. Further, role-playing was reported as an effective method for rehearsing their counselling skills and enhancing quality of intervention delivery. Fidelity feedback through audio-recorded counselling sessions was highlighted as feasible. Considerations around space, location (distance), a lack of privacy, and scheduling were mentioned. The fourth and final theme focused on FBCs' recommendations for improving the project MIND training, supervision and debriefing model, and implementation. FBCs recommended that more time should be allocated for role-playing and skills rehearsal exercises during training to test their counselling skills and readiness. There were some suggestions that the amount of training hours per day should be reduced as it might aid FBCs to remain focused and retain information. Regarding supervision, a few FBCs recommended incorporating occasional peer group supervision and debriefing to benefit from shared experienced. Other recommendations were adding content related to substance use to the intervention and including management in training. Conclusion: Regular structured supervision, debriefing and in-service training provided by a Registered Counsellor are both feasible and beneficial for improving micro-counselling skills and the quality of intervention delivery among FBCs delivering a psychosocial intervention. Considerations for scaling up FBC-led psychosocial interventions should involve addressing barriers such as limited counselling space, remuneration, and marginalization.